Contributions to the aphid fauna (Hemiptera, Aphidoidea) of Chukotka Autonomous Okrug with descriptions of five new species - Stekolshchikov, Andrey V.; Khruleva, Olga A. (Zootaxa, 2015)
The first study of the aphid fauna from Chukotka Autonomous Okrug has been made; 18 species are reported from this territory, the most north-eastern of Russia and of the Palaeartic Region. Five new species are described: Aphis aquilonalis sp. nov. on Rumex arcticus Trautv.; Aphis beringiensis sp. nov. were collected by yellow trap; Macrosiphoniella (Asterobium) jaroslavi sp. nov. on Artemisia arctica Less. and Artemisia tilesii Ledeb.; Macrosiphum chukotense sp. nov., a polyphagous species found on plants in nine different families; and Pleotrichophorus tuberculatus sp. nov. on Artemisia tilesii Ledeb. In addition, the male and oviparous female of Acyrthosiphon boreale Hille Ris Lambers, 1952 and the fundatrix and male of Pleotrichophorus knowltoni Corpuz-Raros and Cook, 1974 are described for the first time.